Managing Occupational Stress in Human Service Nonprofit Organizations in Mykolaiv, Ukraine - Ramonienė, Lineta; Gorbatenko, Olena (Organizations and Markets in Emerging Economies, 2013)
The present research responds to the lack of research on occupational stress in human service nonprofit organizations in Ukraine. The study identified the main stressors in human service nonprofits in Mykolaiv, Ukraine. Then the relationship between occupational stress and the fourteen specific stressors was tested in 11 human service nonprofit organizations in Mykolaiv. The empirical study revealed a positive relationship between occupational stress and eleven stressors. The strongest relationships were observed between job demands that fall short of employees’ skills, and job demands that exceed employees’ time to meet them. Two other stressors – low salary and clients’ trauma – were revealed to be the strongest determinants of stress, accounting for over half of its variation. The study also discovered that employees who work with different client groups experience varying stress levels, and those who work with several groups, as opposed to one, experience more stress. As the first study in human service nonprofit organizations in Mykolaiv and entire Ukraine, the present research lays the groundwork for subsequent research.
Keywords: occupational stress; stressors; nonprofit organizations; human service organizations; Ukraine